2016
DOI: 10.3109/0886022x.2015.1128792
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flexible ureterorenoscopy and mini-percutaneous nephrolithotomy in treatment of lower calyceal stones smaller than 2 cm

Abstract: To compare the outcomes of flexible ureterorenoscopy (F-URS) and mini-percutaneous nephrolithotomy (mini-PNL) in the treatment of lower calyceal stones smaller than 2 cm. Patients who underwent F-URS and mini-PNL for the treatment of lower calyceal stones smaller than 2 cm between March 2009 and December 2014 were retrospectively evaluated. Ninety-four patients were divided into two groups by treatment modality: F-URS (Group 1: 63 patients) and mini-PNL (Group 2: 31 patients). All patients were preoperatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
2
5
1
3
Order By: Relevance
“…Stone free rate in our study was 90.9% in RIRS group as compared with 93.9% in miniPCNL group which was statistically not signicant (p = 0.642). Our results were comparable with study by Fatih Akbulut et al and found to [14] have similar result with 85.7% stone clearance rate in RIRS group and 90.3% in miniPCNL group which was not signicant statistically (p 0.53). Similar results were observed from studies conducted by Sabnis et al , Kirac M et al and Altaf [15] [16] Khan et al with no signicant difference in stone free rate in [17] both groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Stone free rate in our study was 90.9% in RIRS group as compared with 93.9% in miniPCNL group which was statistically not signicant (p = 0.642). Our results were comparable with study by Fatih Akbulut et al and found to [14] have similar result with 85.7% stone clearance rate in RIRS group and 90.3% in miniPCNL group which was not signicant statistically (p 0.53). Similar results were observed from studies conducted by Sabnis et al , Kirac M et al and Altaf [15] [16] Khan et al with no signicant difference in stone free rate in [17] both groups.…”
Section: Discussionsupporting
confidence: 89%
“…21 showed signicantly less hospital stay in RIRS (2.0±1.0 days and 1.9±1.3 days) group compared to miniPCNL (3.5±1.3 days and 4.4±1.4 days) group. Study done by Fatih Akbulut et al also showed results with less hospital stay in RIRS [14] group (22.4±18.2 hours) as compared with miniPCNL group (63.8±32.1 hours) which was statistically signicant (p<0.001).However, study done by Sabnis et al showed no [15] statistical difference in duration of post-operative stay between RIRS and miniPCNL group (p= 0.24)…”
Section: Discussionmentioning
confidence: 92%
“…El tiempo medio para una sesión de LEOC está entre 42.3 ± 6.3 y 48.3 ± 16 (17,19). El tiempo de intervención medio para la CIR varía con el tamaño de la litiasis: con litiasis mayores de 2 cm es de 117.5 ± 28.7 min y con litiasis menores de 2 cm es de 60.8 ± 19.9 min (17,19,(21)(22)(23)(24). Con respecto a la NLP el tiempo medio de intervención es de 73.7 ± 31.3 min y el de la miniperc de 72.1 ± 30.4 min (18,23).…”
Section: Resultsunclassified
“…The impact of metabolic syndrome on the safety and efficacy of flexible ureterorenoscopy nephrolithotomy (PCNL) (4)(5)(6). However, to date, few studies have been available to confirm the safety and efficacy of fURS in patients with metabolic syndrome.…”
Section: Original Articlementioning
confidence: 99%